Connexins and Diabetes. (1st March 2012) - Wright, Josephine A.; Richards, Toby; Becker, David L.
Abstract : Cell-to-cell interactions via gap junctional communication and connexon hemichannels are involved in the pathogenesis of diabetes. Gap junctions are highly specialized transmembrane structures that are formed by connexon hemichannels, which are further assembled from proteins called "connexins." In this paper, we discuss current knowledge about connexins in diabetes. We also discuss mechanisms of connexin influence and the role of individual connexins in various tissues and how these are affected in diabetes. Connexins may be a future target by both genetic and pharmacological approaches to develop treatments for the treatment of diabetes and its complications.